DESIGN OF ONE PHASE ATS (AUTOMATIC TRANSFER SWITCH) USING RELAY-BASED CONTROL AND TIME DELAY RELAY (TDR) - Albert Yosua Panjaitan; Adi Sastra P Tarigan; Solly Aryza (Sean Institute, 2022)
Power outages can disrupt service continuity, especially in service activities in the trade, hospitality, hospital, and industry sectors. Nowadays PLN electricity distribution often fails in distribution due to internal and external factors, to meet the continuity needs of electricity, other electrical energy sources are needed so that if there is a power outage from PLN, consumer needs for electrical energy are not interrupted. These sources of electrical energy are temporary to serve the electrical load in the use of electricity PLN is the main energy source. ATS (Automatic Transfer switch), is a tool that functions to move the connection between one power supply voltage source and another automatically. Or it can also be called Automatic COS (Change Over Switch), in this study a single phase ATS will be designed by reducing the number of Contactors to get more economical and easy results in maintenance. ATS in this study uses a relay-based control circuit and Time Delay Relay (TDR). From the test results, this tool can work well in the switching process manually or automatically. When PLN goes out, there is a delay of time for ± 6 seconds before the generator starts. This aims to keep the components from being damaged if PLN sometimes goes out for a moment.